A simulative comparison of dynamic multi-path routing algorithms for OBS networks - Khan, Farrukh Zeeshan; Hayat, Muhammad Faisal; Holynski, Tomasz (2016 39th International Conference on Telecommunications and Signal Processing (TSP), 2016)
This paper reports extensive simulations of the dynamic routing techniques for optical burst switching (OBS) networks. It gives a summary of the already proposed algorithms and describes more broadly some of them. It introduces also a new one called the Weighted Link Congestion and Frequency (WLCF) algorithm. Our comparative simulations are performed using an in-house developed environment in which all the OBS mechanisms are implemented in detail. Considering various network topologies and traffic scenarios, we show that basically WLCF performs better than other routing strategies in terms of mean burst blocking probability averaged over the whole network, and, thus, increases the overall network throughput.